Efficiency of Carriage Utilization Through the Emphasis of Wagon Turn Around on Hazardous Waste Train: Efisiensi Penggunaan Gerbong Melalui Penekanan Waktu Peredaran Gerbong pada KA Limbah B3 - berliana nur rizky; Kamal, Insan (Jurnal Teknik Transportasi, 2024)
Progress mass transportation that can transport goods in large quantities with a total of 30 wagons is now expanding wings in transportation of hazardous & toxic waste (B3) commodities through the breakthrough of PT Prasadha Pamunah Limbah Industri, PT Kereta Api Indonesia, and PT Kereta Api Logistik with the relation of transporting B3 waste from Kalimas station to Nambo Station. This research aims find out how increase efficiency using flat wagon in B3 Waste transportation & produce an improvement plan that must be done to make use of cars on the B3 Waste train series more efficient. This research method applies a combined approach, which integrates quantitative and qualitative methods order to obtain more comprehensive, valid & reliable data. Data testing in this study was carried out validity test & reliability test with SPSS software, there was also analysis dwelling time & carriage circulation time analysis. Based on analysis can be concluded waiting time for unloading will not be needed so that the loading & unloading time can be reduced to just 1 day if TC Nambo has special heavy equipment for unloading B3 waste, has own heavy equipment operators, expands container yard, increases fleet follow-up trucks to final destination.